Direct Extubation to High-Flow Nasal Cannula versus Noninvasive Ventilation in Obese Subjects. - Magdy, Doaa M.; Metwally, Ahmed (Respiratory Care, 2023)
BACKGROUND: Patients who are obese have a higher risk of acute respiratory failure after extubation in the ICU. This study aimed to compare the extubation of subjects who were critically ill and obese to high-flow nasal cannula (HFNC) versus noninvasive ventilation (NIV) to determine whether HFNC can aid in reducing postextubation respiratory failure and the re-intubation rate. METHODS: In this randomized controlled trial, subjects who were obese, defined as individuals with a body mass index 6 30 kg/m2, were randomly assigned to receive HFNC (n = 60) versus 60 subjects treated with NIV applied immediately after extubation. The primary outcome was the incidence of postextubation respiratory failure and re-intubation rate within 72 h. Secondary outcomes included oxygenation, breathing frequency, subjective dyspnea, ICU and hospital length of stay, and ICU mortality at day 28. RESULTS: Compared with NIV, HFNC reduced the risk of respiratory failure by 8.4%, 95% CI 6.2-12.8%. Even though the rate of re-intubation was lower in the HFNC group versus in the NIV group, no statistical significance was observed (11.6% vs 16.6%; difference 5%, 95% CI 2.5%-8.2%). In 48-h periods and 72 h after extubation, the mean PaO2/FIO2 significantly increased in the HFNC group compared with the NIV group. Both groups had low dyspnea levels 72 h after extubation. No difference was detected between the groups in breathing frequency. In addition, the 2 groups had no significant difference in ICU and hospital length of stay. The HFNC and NIV groups had comparable hospital mortality rates. The multivariable logistic regression analysis revealed the presence of severe obesity, comorbidities, a higher severity score, and hypercapnia remained as factors associated with an increased risk of re-intubation. CONCLUSIONS: Postextubation application of HFNC may prevent respiratory failure in patients who are obese. (ClinicalTrials.gov registration NCT04035351.)